NUTRITIONAL AND PHYSICOCHEMICAL CHARACTERIZATION OF SELECTED DROUGHT TOLERANT NIGERIAN LOCAL RICE CULTIVARS - Charles Osuji; Daniel Haruna (Journal of Experimental and Molecular Biology, 2025)
Drought-tolerant rice cultivars with inherent good quality traits are important in ensuring adequate and nutritious food for humans, particularly in sub-Saharan African regions like Nigeria. Thus, for the attainment of effective nutrition security in a climate-changing world, it is expedient to scientifically characterize, identify, and develop good quality rice cultivars with intrinsic drought tolerance potentials. In this study, four potentially drought-tolerant rice cultivars were collected from local rice farmers in some Northern parts of Nigeria. They were first subjected to preliminary drought tolerance validation, then physicochemical, proximate, mineral, and transgene diagnostic analyses. The proximate analysis results showed that the cultivars have good protein content particularly “Nassarawa-Lafia” (10.20±0.00%) while “Jigawa-Mafa” has the highest fiber and magnesium content of 1.81±0.01% and 31.80±0.04% respectively. Mineral content analysis results also revealed cultivars like “Jigawa-Mafa” and “Nassarawa-Lafia” as high potassium enriched up to 118.72±0.41mg/100g and 117.06±0.91mg/100g. The molecular diagnostics showed no transgene presence in all the samples. These findings highlight the good nutritional qualities of the cultivars and their potential health benefits. This calls for a more in-depth search of the expansive local genetic pool for crops with promising abilities for cultivation and subsequent breeding programs to address the increasing food and nutrition challenges.